Annual competition for essay writing in Danish language - Atanasova, Gabriela; Temelkova, Ivon; Zagareva, Beloslava; Velikov, Velislav (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
The annual competition for essay writing in Danish language has been organized since 2015 by the Hans Christian Andersen Centre for Research and Information at Sofia University St. Kliment Ohridski, the Embassy of Denmark in Sofia and the Danish Agency for Culture and Palaces (Slots- og Kulturstyrelsen).